Impact of the covid-19 on the production and consumption of vegetables in southeast Pará (Research, Society and Development, 2021)
The aim of this study was to evaluate the profile of vegetable producers and consumers in the cities of Xinguara and Rio Maria in the state of Pará. Semi-structured questionnaires were used in the interviews that were carried out in remote format on different digital platforms. Most vegetable farmers in the counties interviewed 70% are men, over 31 years of age, have been working in agriculture for more than six years and work between five to eight hours/day growing vegetables, with the majority residing within the urban perimeter. The production of leafy vegetables prevails, with 80% of those interviewed using less than one hectare of the area for planting in the semi-intensive system and mainly commercialized at open-air markets. The Covid-19 pandemic interfered in production and marketing in 80% of rural producers, with a decrease between 10% and 70%. The frequency of purchase of vegetables by respondents is once a week, with weekends being the days chosen to purchase fresher products. The most consumed vegetables are lettuce, cabbage, chives, cilantro and tomato, and purchases are preferably made in the morning, in supermarkets, and the average family expense is up to R$30.00/week. Price and quality are among the most important requirements when purchasing products. With the Covid-19 pandemic, most consumers did not stop consuming vegetables, but a small portion of respondents had to reduce consumption by up to 10% due to the decrease in family income.